2018
DOI: 10.1111/1756-185x.13271
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in retention rate of tumor necrosis factor alpha inhibitor treatment in ankylosing spondylitis: a retrospective cohort study in daily practice

Abstract: AimTo assess gender differences in ankylosing spondylitis (AS) patients in relation to tumor necrosis factor alpha inhibitor (TNFi) drug survival and occurrence of adverse events in daily practice in a large peripheral hospital.MethodRetrospective data were collected from AS patients treated with etanercept, infliximab and adalimumab between January 2004 and January 2014. Kaplan–Meier survival curves were conducted to describe the drug survival and occurrence of adverse events in time.ResultsOverall, 122 AS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
3
23
1
Order By: Relevance
“…Regarding the reason for ADA discontinuation, lack of drug efficacy is more frequent in males than in females. Our data are in contrast with those reported by literature showing that treatment efficacy of TNFi in SpA was lower in women compared to men and that switching TNFi treatment was more frequent in female than in male patients (Rusman et al, 2018a,b). In this regard, one important limitation of our retrospective study is the lack of information regarding a range of variables able to impact TNFi response, such as smoking, body mass index, and glucocorticoid use.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding the reason for ADA discontinuation, lack of drug efficacy is more frequent in males than in females. Our data are in contrast with those reported by literature showing that treatment efficacy of TNFi in SpA was lower in women compared to men and that switching TNFi treatment was more frequent in female than in male patients (Rusman et al, 2018a,b). In this regard, one important limitation of our retrospective study is the lack of information regarding a range of variables able to impact TNFi response, such as smoking, body mass index, and glucocorticoid use.…”
Section: Discussioncontrasting
confidence: 99%
“…Of note, both SpA and IBD are characterized by the presence of sex differences in their onset, progression and response to therapy (Rusman et al, 2018a,b; Shah et al, 2018). Regarding TNFi, differences between males and females in response to these drugs have recently been suggested, with males responding better than females (Gonzalez-Lama et al, 2008a,b; Olivera et al, 2017; Rusman et al, 2018a,b). However, the relationship between sex and response to TNFi in SpA and IBD is far to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α is an important proinflammatory factor mainly produced by mononuclear macrophages, and is involved in a series of immune responses (35). A previous study suggested that TNF-α was important for the inflammatory response to AS (36). In the present study, it was revealed that TNF-α inhibitor attenuated the inflammatory response of PBMCs in patients with AS by suppressing IL-6 expression and promoting IL-10 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Data from observational cohort studies suggest that TNF inhibitors for psoriatic arthritis are more effective in male than female patients, even when controlling for confounding variables, including comorbidities (e.g., chronic pulmonary disease) and lifestyle (e.g., smoking) [25]. Females also are less likely than males to adhere to treatment with TNF inhibitors for spondyloarthritis, with lack of efficacy and adverse events being associated with immunotherapy withdrawal among females [24,26].…”
Section: Male-female Disparities In Immunotherapiesmentioning
confidence: 99%